Targeting exercise interventions to patients with cancer in need: an individual patient data meta-analysis - Buffart, Laurien; Steindorf, Karen; Bohus, Martin; Schmidt, Martina; Potthoff, Karin; Wiskemann, Joachim (Journal of the National Cancer Institute, 2018)
Exercise effects in cancer patients often appear modest, possibly because interventions rarely target patients most in need. This study investigated the moderator effects of baseline values on the exercise outcomes of fatigue, aerobic fitness, muscle strength, quality of life (QoL), and self-reported physical function (PF) in cancer patients during and post-treatment.